Evaluation of Office and Ambulatory Central Blood Pressure and Augmentation Index by Two Methods and Their Changes After Lifestyle or Medical Interventions in Hypertension - Helga Gyöngyösi; Dóra Batta; Andrea László; Péter Torzsa; Beáta Kőrösi; Zsófia Nemcsik-Bencze; Orsolya Cseprekál; András Tislér; János Nemcsik (Artery Research)
Abstract Objective Central systolic blood pressure (cSBP) and augmentation index (Aix) can be evaluated in office and also in ambulatory condition, during 24-h monitoring. The aim of our study was to measure cSBP and Aix in the office and in 24-h setting cSBP with two calibration methods and also Aix. Thereafter, we aimed to compare their changes after the initiation of lifestyle modifications or antihypertensive medications. Methods Office cSBP and Aix were measured with the tonometric PulsePen device (PP-cSBP, PP-Aix, respectively), while 24-h ambulatory cSBP and Aix (24 h-Aix) were evaluated with Mobil-O-Graph. For the calculation of 24-h cSBP both systolic/diastolic and systolic/mean BP calibration methods were considered (24 h-cSBPC1 and 24 h-cSBPC2, respectively). In new hypertensive patients (HT) the measurements were repeated 3 months after the initiation of antihypertensive medication while in white-coat hypertensive patients (WhHT) 12 months after lifestyle modifications. Results 105 patients were involved including 22-22 HT and WhHT subjects, respectively. PP-cSBP (128 ± 13 mmHg,) was higher than 24 h-cSBPC1 (118 ± 9 mmHg, p < 0.05), but equal with 24 h-cSBPC2 (131 ± 11 mmHg). PP-Aix (14 ± 14%) was lower than 24 h-Aix (22 ± 7%, p < 0.05). For medical intervention PP-cSBP (Δ16 mmHg) decreased more, than 24 h-cSBPC1 (Δ10 mmHg, p < 0.05) and 24 h-cSBPC2 (Δ9 mmHg, p < 0.05). Conclusions Office tonometric and 24 h oscillometric cSBP values differ depending on the calibration. When examining the effect of antihypertensive treatment, the more marked changes in office tonometric cSBP suggests its higher variability compared with 24 h oscillometric central SBP. During follow-up, the two calibration methods of 24 h-cSBP seems not to be interchangeable.